Beliefs and practices of diabetic patients in Vhembe district of Limpopo Province - Hilda Shilubane; Lizzy Netshikweta; Tshinyadzo Ralineba (AOSIS, 2016)
Background: Diabetes mellitus (DM) is a chronic condition affecting over 18 million people worldwide. It can lead to debilitating complications and premature death if not effectively controlled. South Africa, like any sub-Saharan countries and the world at large, is no exception. The prevalence of diabetes among South African adults has increased by 50% from 2009 to date, and an increase of some 11 million new diabetes diagnoses is expected by the year 2020. Purpose: The purpose of this study was to describe the beliefs and management practices of patients with DM in Vhembe district, Limpopo province. Setting: The study was conducted at Vhembe district clinics. Methods: A probability, purposive sampling was used to sample 100 diabetic patients. Data were collected using a pre-tested questionnaire. Data were analysed using the Statistical Package for Social Sciences version 19.0. Descriptive statistics, frequencies, and percentages were used to summarise the data from the study. Results: The majority of the respondents had poor management practice of feet care and annual eye examinations. Twenty four (24.0%) of the respondents believed that DM can be cured and 22 (22.0%) did not believe that diet helps in the management of DM. Conclusion: The belief that DM is curable can have a negative effect as patients can quit taking treatment once the disease is under control. This happens irrespective of the national guidelines for the management of DM. Therefore, some strategies should be sought that could enhance the implementation of the guidelines in order to combat the disease.